2013
DOI: 10.1007/s11064-013-1230-x
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Fear Conditioning in Maternal Separated Rats: The Amygdala as a Site for Alterations

Abstract: The first 2 weeks of life are a critical period for neural development in rats. Repeated long-term separation from the dam is considered to be one of the most potent stressors to which rat pups can be exposed, and permanently modifies neurobiological and behavioral parameters. Prolonged periods of maternal separation (MS) usually increase stress reactivity during adulthood, and enhance anxiety-like behavior. The aim of this study was to verify the effects of maternal separation during the neonatal period on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 76 publications
4
13
0
Order By: Relevance
“…By contrast, ELS treatment decreased freezing behavior in female mice, suggesting that ELS hampers contextual fear memory formation. This agrees with several studies using rat models for early life adversity (Chocyk et al, 2014 ; Sun et al, 2014 ; Xiong et al, 2014 ), but other studies reported either no effect (Kosten et al, 2006 ; Diehl et al, 2007 ; Oomen et al, 2011 ) or even an enhanced contextual fear conditioning (Diehl et al, 2014 ). This suggests that various models of early life adversity or species differences may determine the effect of early life adversity on contextual fear.…”
Section: Discussionsupporting
confidence: 90%
“…By contrast, ELS treatment decreased freezing behavior in female mice, suggesting that ELS hampers contextual fear memory formation. This agrees with several studies using rat models for early life adversity (Chocyk et al, 2014 ; Sun et al, 2014 ; Xiong et al, 2014 ), but other studies reported either no effect (Kosten et al, 2006 ; Diehl et al, 2007 ; Oomen et al, 2011 ) or even an enhanced contextual fear conditioning (Diehl et al, 2014 ). This suggests that various models of early life adversity or species differences may determine the effect of early life adversity on contextual fear.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, a strong increase in behavioral fragmentation was observed in MS dams, and the offspring also exhibited very different corticosterone secretion patterns compared to controls. Male MS rats did not increase corticosterone production in response to the aversive context exposure, since their basal levels were already high; this may correlate with the increase in anxiety-like behavior and memory processing changes previously reported in MS male Wistar rats (Aisa et al, 2007;Diehl et al, 2011Diehl et al, , 2014. MS females, on the other side, had lower basal corticosterone levels than controls, as previously reported also in Wistar rats (Diehl et al, 2007;Llorente-Berzal et al, 2012), and showed a marked increase after the challenge.…”
Section: Discussionsupporting
confidence: 82%
“…It has been recently suggested that increased maternal care, when analyzed purely quantitatively, is not necessarily favorable to litter development (Dalle Molle et al, 2012; Murgatroyd and Nephew, 2013; Reeb‐Sutherland and Tang, 2012). This idea contributes to the discussion of why MS offspring, despite having over caring mothers, have such deleterious stress responses as adults (Aisa et al, 2007; Desbonnet et al, 2008; Diehl et al, 2014, 2011; Lajud et al, 2012; Rivarola and Suárez, 2009). In addition, raises the question of how much and what maternal care features are relevant to the long time consequences of handling and maternal separation on offspring.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that postnatal maternal separation led to long-lasting hyperactivity of neuroendocrine hypothalamic-pituitary-adrenal (HPA) axis and abnormal passive stress coping and memory, which was associated with the persistent upregulation of the expression of arginine vasopressin due to the sustained DNA hypomethylation of the promoter region of Avp in mice [2]. Repeated maternal separation during postnatal days 1–10 significantly lowered the behavioral performance in the contextual fear conditioning test in the rats at postnatal day 60 [3]. Currently the epigenetic mechanism underlying the postnatal maternal separation-induced memory deficiency remains speculative in the rodent model.…”
Section: Introductionmentioning
confidence: 99%